Review of literature on the use of mango seed for oil extraction and its potential applications in various industries - Córdova Córdova, Antonio Martín (2021)
This research aims to demonstrate through a review of literature the existence of industrial applications for mango seed oil (MSO) since it has comparable and even better physique-chemical properties than other oilseed oils. The revised articles indicate that the MSO is edible, of high quality, rich in unsaponifiable matter, and consisting mainly of stearic and oleic fatty acids. It also reveals the great potential of MSO as cocoa butter substitute, natural antioxidant, cosmetic, antimicrobial compound, and even biofuel. These applications will enable industries to generate more significant economic benefits and will contribute to the care of the environment.